Performance of density functional theory on the anisotropic halogen···halogen interactions and potential energy surface: Problems and possible solutions. Issue 9 (12th February 2016) - Liu, Fang; Du, Likai; Zhang, Dongju; Gao, Jun
Abstract : The noncovalent halogen···halogen (X···X) interaction, which shows significant anisotropic feature, is extensively used in rationally designing supramolecular assemblies. Here, beyond the binding energy of stable geometries, the anisotropic topology of the potential energy surface (PES) is explored. We show that most functionals of DFT give remarkably unphysical angular distortion of the PES. This is unlikely to be solved unless the components that ensure correct angular dependent behavior in the halogen bonding region are contained in the functionals. We also prove that simple empirical corrections may substantially quantify this unphysical angular distortion, and further investigation is recommended. These findings constitute a step forward toward the understanding of the nature of X···X bonds, and provide some insights for the future designing of the state‐of‐art theoretical methods. © 2016 Wiley Periodicals, Inc. Abstract : The understanding of the potential energy surface of noncovalent halogen···halogen interactions, and in particular its anisotropic topology, is extensively used in rationally designing supramolecular assemblies. Theoretical results show that most DFT functionals require further improvement to ensure the correct angular dependent behavior in the halogen bonding region. A simple empirical correction may substantially quantify this unphysical angular distortion.